A familial incidence of Otosclerosis - Tlruvenkatachari (Journal of All India Institute of Speech and Hearing, 1970)
Carhart  (1963)  reports  a  family   wherein   two   brothers  were   suffering from labyrinthine otosclerosis.   Their mother had a long standing hearing loss and their own difficulties had been progressive since the ages of 11 and 15 res- pectively and the younger man exhibited a lower level of hearing loss.   Their audiograms showed bilateral mixed hearing loss.